Influence of FecB gene in greasy fleece yield in Malpura, Garole and their crossbreeds - PATIL, KAVITA; ULMEK, B R; ARORA, A L (The Indian Journal of Animal Sciences, 2012)
FecB gene played important role in GFY1. However improvement in GM crosses with regards to growth traits was very slow as compared to the Malpura. Therefore back- crossing of GM crosses with Malpura ram or ewe might be useful for improving production and reproduction traits.